Promoting low-carbon investment (UN New YorkUS, 2013)
Aims to help IPAs , especially those in developing countries, to promote foreign investment with a view to maximising the sustainable development impact on their host economies. Focuses on practical guidelines for identify, targeting and servicing investors in line with defined developed objectives.
Keywords: GREEN REVOLUTION